Multiple equipment scheduling and AGV trajectory generation in U-shaped sea-rail intermodal automated container terminal. (January 2023) - Liu, Wenqian; Zhu, Xiaoning; Wang, Li; Wang, Shuai
Highlights: U-shaped layout is compared with traditional layout in automated container terminal. Landside and quayside operations are considered simultaneously in multi-objective model. A bi-level GA with greedy strategy is designed based on the topological network. AGV running characteristics are analyzed in light of spatio-temporal trajectories. Abstract: As a key development direction of future ports, automated container terminals will play a crucial part in the development of multimodal transportation. Based on the newly constructed U-shaped yard layout in sea-rail intermodal container terminal, this paper focuses on the integrated scheduling of horizontal transport equipment and handling equipment, as well as path planning for AGVs. A bi-level programming model is established to obtain the yard crane scheduling scheme and determine the specific trajectories of AGVs with the goal of minimizing the makespan and total waiting time of AGVs and trucks. We design a spatio-temporal greedy strategy based bi-level genetic algorithm to schedule tasks and resolve conflicts in light of the multi-objective and hierarchical characteristics of the problem. Results indicate that the proposed algorithm could resolve the path conflicts effectively and obtain the integrated scheme that hardly affect the operation process of sea-rail intermodal containers.